China’s Employment Discrimination Laws during Economic Transition - Brown, Ronald C. (Columbia Journal of Asian Law, 2006)
While working as a consultant to the World Bank on China’s labor legislation in 1996, I was waiting outside the gate of the Ministry of Labor, when I noticed a job advertisement posted on a pole. It read, Seeking an office clerk. Female, decent height and appearance. All five facial organs must be in the right place (wu guan duan zheng). In 2005, job advertisements with identical facial requirements are widely seen. That, of course, is but one frank articulation of what many employers around the world take note of in the employment hiring process. Other factors in considering applicants and employees in China may include sex, ethnicity, social origin, health, disability, age, or migrant status, some of which are considerations prohibited by Chinese labor laws. This article describes the current status of the above factors as used in human resource management (HRM) practices during China’s current economic transition, and further examines China’s existing anti- discrimination labor legislation. Some comparative references are made to labor standards under International Labor Organization (ILO) Conventions and U.S. legislative approaches. This article further suggests areas for legal reform to both clarify coverage and enhance enforcement and remedies, which would in turn arrest some of the more pernicious illegal hiring and employment practices currently found in China’s HRM.